Reduced density matrix and combined dynamics of electrons and nuclei - Zhao, Yang (2011)
Nuclear dynamics is incorporated into an efficient density matrix formalism of electronic dynamics which has been applied to molecular systems containing thousands of atoms. The formalism for the combined dynamics of electrons and nuclei is derived from the Dirac–Frenkel variational principle. The single electron reduced density matrices and the Glauber coherent states are used for the electronic and nuclear degrees of freedom, respectively. The new formalism is applicable to simulate the dynamics of large molecular systems. As an illustration of its validity, the formalism is employed to calculate the electron and nuclei dynamics of hydrogen molecules.